Penentu Kebijakan Dividen Perusahaan yang Sahamnya Masuk dalam Daftar Efek Syariah - Khoiruddin, Moh; Setiowati, Yuni (IAIN Salatiga, 2013)
This study purpose to the determine the influence of Current Ratio, Debt to Equity Ratio, Earning Per Share, and Return On Assets to the Dividend Policy (Dividend Payout Ratio) for companies included Daftar Efek Syariah period 2008-2010 simultaneously and partial. The population in this study all companies included Daftar Efek Syariah period 2008-2010 amount to 286 companies. The sample selection procedure used was a purposive sampling so that it produced 44 companies. Secondary data was collected by the documentation technique were obtained from the fundamental annual report 2011. The analysis technique used was multiple linear regression analysis using the tools of SPSS. The research found that four variables of kind of CR, DER, EPS and ROA simultaneously influence to DPR for companies included Daftar Efek Syariah period 2008-2010. The three variables of kind of CR, EPS, and ROA partially influence positive significant to DPR, while variable DER influence negative but insignificant to DPR for companies included Daftar Efek Syariah period 2008-2010.